Analysis of Runway Pavement Thickness Using FAA and LCN Methods - Yacub, Garin; Aulia, Askia Esa; Birahmatika, Lilla Anjani; Purba, Jhon Hardy (Syntax Literate, 2026)
Runways are crucial components of airport air transportation systems, serving as the primary surfaces for aircraft takeoffs and landings. To withstand the repetitive loading from various aircraft types, runway pavements must be designed with precise thickness in accordance with applicable technical standards. Despite the availability of various design guidelines, a notable research gap exists in the comparative evaluation of these methods for high-traffic runways to balance structural safety with modern economic and environmental sustainability goals. This study addresses this gap by analyzing the pavement thickness of Runway 3 at Soekarno-Hatta International Airport using two widely applied calculation methods: the Federal Aviation Administration (FAA) method and the Load Classification Number (LCN) method. The analysis utilized secondary data obtained directly from PT Angkasa Pura II, encompassing the dominant aircraft type (Boeing 737-800), annual aircraft movement volume, subgrade California Bearing Ratio (CBR) value (6%), and the specifications of the applied pavement materials. Calculations indicate that the FAA method requires a total pavement thickness of 990 mm, whereas the LCN method yields a lower thickness requirement of 889 mm. These findings demonstrate that the LCN method is more efficient than the FAA method within the context of Runway 3. The practical implications of this 101 mm difference in thickness are highly significant; the application of the LCN method directly contributes to reduced construction costs, minimizes material consumption, and supports sustainability objectives by lowering carbon emissions during the production and construction phases. In conclusion, this study strongly recommends the adoption of the LCN method in the development of modern airport infrastructure, as it has proven capable of meeting stringent safety standards while comprehensively optimizing economic efficiency and infrastructure sustainability.